2018
DOI: 10.1002/sctm.18-0085
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-Seeded Biomimetic Scaffolds as a Factory of Soluble RANKL in Rankl-Deficient Osteopetrosis

Abstract: Biomimetic scaffolds are extremely versatile in terms of chemical composition and physical properties, which can be defined to accomplish specific applications. One property that can be added is the production/release of bioactive soluble factors, either directly from the biomaterial, or from cells embedded within the biomaterial. We reasoned that pursuing this strategy would be appropriate to setup a cell-based therapy for RANKL-deficient Autosomal Recessive Osteopetrosis, a very rare skeletal genetic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…In vitro osteoclastogenesis was induced following standard protocols, as reported . Briefly, 4 × 10 5 splenocytes/well were cultured in 96‐well plates in α‐MEM medium (Sigma‐Aldrich) supplemented with 10% FBS, 1% penicillin/streptomycin (P/S), and 1% glutamine in the presence of 25 ng/mL murine M‐CSF, 5 ng/mL human TGFβ1 (both from Peprotech, London, UK), 1 μM dexamethasone (Sigma‐Aldrich), and with or without 100 ng/mL RANKL for 6 days.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro osteoclastogenesis was induced following standard protocols, as reported . Briefly, 4 × 10 5 splenocytes/well were cultured in 96‐well plates in α‐MEM medium (Sigma‐Aldrich) supplemented with 10% FBS, 1% penicillin/streptomycin (P/S), and 1% glutamine in the presence of 25 ng/mL murine M‐CSF, 5 ng/mL human TGFβ1 (both from Peprotech, London, UK), 1 μM dexamethasone (Sigma‐Aldrich), and with or without 100 ng/mL RANKL for 6 days.…”
Section: Methodsmentioning
confidence: 99%
“…The secretome of MSCs also includes extracellular vesicles, which contain proteins and μRNAs that control target cell function. There are multiple examples of therapeutic effects of MSCs in preclinical models that are attributed to the MSC secretome, such as for instance the inhibition of colitis via the release of tumor necrosis factor‐induced protein 6 by intraperitoneal administered MSCs or via the release of the osteoclastogenic factor Receptor Activator of Nuclear factor Kappa‐B Ligand by MSCs seeded on biomimetic scaffolds for the treatment of osteopetrosis . Other studies have demonstrated that the effects of MSCs can be mimicked by infusion of MSC conditioned culture medium .…”
Section: Mechanism Of Action; Current State Of the Artmentioning
confidence: 99%
“…Osteoclasts differentiated on bone slices were stained using alendronate conjugated to Alexa Fluor 488 24 , TRITC-conjugated phalloidin (Sigma-Aldrich) and TO-PRO-3 (Thermo Fisher Scientific). To evaluate bone resorption, the same bone slices were used for toluidine blue staining as previously described 25 . TRAP and toluidine blue images were acquired on a Zeiss AxioImager…”
Section: Rnaseq Total Rna Of Cd34+ Cells Was Extracted Using Reliaprmentioning
confidence: 99%